Indigenous investments: Are they different? Lessons from Iwi*. Issue 2 (May 2021) - Poyser, Andre; Scott, Ayesha; Gilbert, Aaron
Iwi, the tribal entities of the Māori people of Aotearoa New Zealand, now manage billions of dollars, a task requiring increasing sophistication in their investment strategies. Asset classes of Iwi have evolved from the properties, fisheries quotas, and cash they received through Aotearoa New Zealand's Treaty settlement process to now include major investments in private equity, infrastructure, and other financial assets. The literature has, however, been largely silent on Iwi investments. Performance discussions tend to emphasize a western approach focusing on traditional financial performance measures. Using Waikato-Tainui operated Tainui Group Holdings (TGH) as an example, we analyze a sample of corporate disclosure documents. We find the intent of tribal (Iwi) investment firms may not be adequately captured through traditional investment frameworks and classic performance metrics. Drawing parallels between Iwi investment firms and impact investing widens the scope for financial managers to think differently about how we quantify Indigenous investment performance.